Kupffer Cells: Important Participant of Hepatic Alveolar Echinococcosis - Liu, Yumei; Tian, Fengming; Shan, Jiaoyu; Gao, Jian; Li, Bin; Lv, Jie; Zhou, Xuan; Cai, Xuanlin; Wen, Hao; Ma, Xiumin (Frontiers in Cellular and Infection Microbiology, 2020)
Aims: Kupffer cells (KCs) are the liver-resident macrophages and play a leading role in the regulation of liver homeostasis in physiological conditions and in pathology. The study aims to investigate the anti-echinococcosis effect of KCs and the effects of hepatic stellate cells (HSCs) activation in the progression of liver fibrosis in hepatic alveolar echinococcosis (hepatic AE). Methods: Hematoxylin—eosin (H&E) and Masson staining were used to assess the pathological inflammatory changes and collagen deposition, respectively. Immunohistochemistry and qRT-PCR were used to detect the number of aggregates of KCs, the expression of cytokines and activation of HSCs. Results: In the close group, H&E staining showed that the normal lobular structure was destroyed and inflammatory infiltration around the lesion could be observed, and Masson staining showed that blue collagen fibers were clearly deposited near the portal area. IHC showed that KCs surface markers CD68 and CD163, cytokine iNOS and Arg-1 were positively expressed in the vicinity of inflammatory lesions. qRT-PCR indicated that TNF-α, IL-10, and TGF-β1 secreted by KCs were significantly higher than those in the distance group (P < 0.01). It is worth noticing that the expression levels of anti-inflammatory cytokines were slightly higher than that of pro-inflammatory cytokines. Both IHC and qRT-PCR results showed that HSCs activation markers, the expression of α-SMA and Desmin significantly increased. Conclusions: Our research indicates that KCs have immune-protective effect of anti-echinococcosis and promote liver fiber repair, and it also suggests that they have potential therapeutic value for patients with hepatic AE.